New molecular features of cowpea bean (Vigna unguiculata, l. Walp) beta-vignin - Ferreira, Ederlan de Souza; Capraro, Jessica; Sessa, Fabio; Magni, Chiara; Demonte, Aureluce [UNESP]; Consonni, Alessandro; Neves, Valdir Augusto [UNESP]; Cilli, Eduardo Maffud [UNESP]; Duranti, Marcello; Scarafoni, Alessio (Taylor & Francis Ltd, 2018)
Cowpea seed -vignin, a vicilin-like globulin, proved to exert various health favourable effects, including blood cholesterol reduction in animal models. The need of a simple scalable enrichment procedure for further studies for tailored applications of this seed protein is crucial. A chromatography-independent fractionation method allowing to obtain a protein preparation with a high degree of homogeneity was used. Further purification was pursued to deep the molecular characterisation of -vignin. The results showed: (i) differing glycosylation patterns of the two constituent polypeptides, in agreement with amino acid sequence features; (ii) the seed accumulation of a gene product never identified before; (iii) metal binding capacity of native protein, a property observed only in few other legume seed vicilins.
Keywords: Vigna ssp; vicilin proteins; beta-vignin; glycosylation; metal ion binding